Proof of stake-based blockchain applications - Fecho, Tyrone Jiale (2019)
This project aims to explore the benefit of Proof of Stake and implements demonstrative IoT ( Internet of Things ) applications using blockchain technology. The system designed incorporates a Python application running on a Windows platform, an Android application running on Python and a local Wi-Fi network. Together, this project can simulate multiple devices on a network and, run an actual mobile device with the network. This report will present and explain the design used and recommendations for future work.